Proteomic characteristics of human sperm cryopreservation. Issue 2 (February 2014) - Wang, Shangqian; Wang, Wei; Xu, Yang; Tang, Min; Fang, Jianzheng; Sun, Hongyong; Sun, Yangyang; Gu, Meijuan; Liu, Zhili; Zhang, Zhaoxia; Lin, Faxi; Wu, Ting; et al.
<x xml:space="preserve">Abstract</x> Human sperm cryopreservation in assisted reproductive technology is the only proven method that enables infertile men to father their own children. However, freezing and thawing reduces spermatozoon motility, viability, and fertilizing ability. An association between dysfunctional spermatozoa due to cryoinjury and protein changes has not been established. We investigated through proteomic analysis the differential protein characteristics between freeze‐thawed and fresh sperm samples obtained from nine normozoospermic donors. Twenty‐seven proteins differed in abundance between the two groups, and results were verified for four proteins via Western blot and immunofluorescent staining. These proteins are putatively involved in sperm motility, viability, acrosomal integrity, ATP and isocitrate content, mitochondrial membrane potential, capacitation, acrosome reaction, and intracellular calcium concentration. These marked differences suggest that dysfunctional spermatozoon after cryopreservation may be due to protein degradation and protein phosphorylation.